Balancing the books or winning votes: unveiling the power of fiscal strategies in local elections and the fate of prudent mayors - Krzysztof Kluza; Hanna Kociemska; Wojciech Rafał (Regional Studies, Regional Science)
This research examines how mayors’ fiscal decisions affect their likelihood of re-election, with a particular focus on their use of political business cycle tactics during local elections. The theory suggests that there are some incentives for incumbents to manipulate fiscal policy at the local level. The study examines the budgets of 2475 local government units in Poland over 15 years, covering three full local election cycles, using a panel data logit model to assess the influence of their fiscal activity on re-election outcomes. The results show that increasing deficits or investments in election years can significantly improve the re-election prospects of mayors, with a stronger effect for investments. However, investment is less susceptible to short-term changes and deficits are easier to influence. Increasing the deficit raises the likelihood of re-election by about 80% (odds ratios), while running large budget surpluses through reduced spending can effectively eliminate the chances of re-election. Furthermore, increasing debt has no significant effect on re-election chances. The research also examines which categories of local government are most likely to exhibit incumbency behaviour consistent with political business cycle theory. The overall analysis highlights the complex relationship between fiscal policy choices and electoral victory in local government. It provides insights into political strategies and their consequences for political accountability and fiscal responsibility. The research findings suggest the need for additional checks and balances, such as deficit ceilings, to counteract politically motivated fiscal mismanagement and underline the importance of fiscal responsibility in local governance.